2022
DOI: 10.1055/s-0042-1742634
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Profile of Patients with Bloodstream Infections Caused by Burkholderia cepacia Complex

Abstract: Introduction Burkholderia cepacia complex (BCC) is an emerging pathogen causing nosocomial bloodstream infections (BSIs), and its treatment is challenging due to its multidrug resistance. In India, there is a dearth of data on BSIs caused by BCC, therefore, an updated study is required to know the clinical and microbiological profile of these patients. We aimed to study the clinical epidemiology and antibiotic susceptibility pattern of BCC isolated from blood samples in our hospital. Materials and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
3
3
0
1
Order By: Relevance
“…B. cepacia isolates in the present study remain high sensitivite to ceftazidime (92.7%) and cefoperazone (76.9%). These antibiotic susceptibility results showed similarity with others signifying the high sensitivity Burkholderia cepacia to ceftazidime and/or cefoperazone ( 13 , 17 , 25 ). The use of surveillance programs and careful administration of antibiotics can help prevent the spread of B. cepacia infections, even though some medications are still effective against it.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…B. cepacia isolates in the present study remain high sensitivite to ceftazidime (92.7%) and cefoperazone (76.9%). These antibiotic susceptibility results showed similarity with others signifying the high sensitivity Burkholderia cepacia to ceftazidime and/or cefoperazone ( 13 , 17 , 25 ). The use of surveillance programs and careful administration of antibiotics can help prevent the spread of B. cepacia infections, even though some medications are still effective against it.…”
Section: Discussionsupporting
confidence: 84%
“…This is in accordance with previous study demonstrated that B. cepacia were the most commonly found in blood specimens accounting for which was associated with bloodstream infections ( 15 , 16 ). Moreover, other investigators highlighted the prevalence of B. cepacia detected in 30 patients with bloodstream infections during two-year period ( 17 ) indicating B. cepacia as emerging pathogens in blood stream infections. Furthermore, B. cepacia as BSI pathogens are also prevalently detected in patients with central venous catheters.…”
Section: Discussionmentioning
confidence: 98%
“…The results of Burkholderia cepacia complex showed that isolate had given a result at negative for indole .But positive for methyl red , voges proskauer , urease test , citrate assimilation , motility ,catalase and oxidase ,TSI alkaline / acidic with no production of H2S and gas. Similar finding were recorded by [17]. The percentage of all other bacterial growth, which was isolated in this results are consistent with findings from other Iraqi studies [18,19].…”
Section: Resultssupporting
confidence: 93%
“…[23,24,25] Kady et al reported B. cepacia isolates to be 100% susceptible to meropenem, ceftazidime, cotrimoxazole, and minocycline. [26] In the present study, 23 The results obtained in the present study are concordant to Baidya et al, Rewdiwala et al and Kaur et al…”
Section: Resultssupporting
confidence: 91%